Post-chemoradiotherapy adjuvant chemotherapy of rectal cancer - E. V. Ledin; A. V. Kochatkov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
The aim of review. To present the analysis of available data on approach to pharmacological antineoplastic therapy at rectal cancer (RC) after chemoradiotherapy followed by surgical treatment, as well as within the «watch & wait» concept. Summary. The present time adjuvant chemotherapy is the standard of treatment for III stage rectal cancer after preoperative chemoradiotherapy and surgery. However according to detailed analysis, in this group of patients adjuvant chemotherapy has inconsistent results and no clear-cut advantage can be found at absence of lymph node involvement according to histological study or complete tumor regression due to preoperative chemoradiotherapy. The meta-analysis (2015) of 4 randomized third-phase clinical trials (EORTC 22921, I-CNR-RT, PROCTORSCRIPT, CHRONICLE) demonstrated the lack of significant of 5-fluorouracil-based adjuvant chemotherapy. Efficacy of 5-fluorouracil monotherapy was directly compared to 5-fluorouracil with oxaliplatin combination in several randomized trials. Results of the studies indicate that patients with stage ypI or complete morphological response obtain no significant advantage from adjuvant chemotherapy. The same conclusion can be drawn concerning patients with postponed or cancelled surgery who received treatment within «watch & wait» program. At meta-analysis of 12 studies implementing «watch & wait» protocol with subsequent chemotherapy no definite advantages of adjuvant chemotherapy were demonstrated as well. On the other hand, 5-fluorouracil and oxaliplatin-based chemotherapy should be recommended to patients with ypIII stage of the disease and II stage patients having risk factors. Conclusion. The decision to prescribe adjuvant chemotherapy seems to be correct in relation to pathologic study results and degree of preoperative chemoradiotherapy response.